Nitric Oxide Enables Germination by a Four-Pronged Attack on ABA-Induced Seed Dormancy - Signorelli, Santiago; Considine, Michael J. (Frontiers in Plant Science, 2018)
Nitric oxide (⋅NO) is known to attenuate dormancy and promote germination, a function that seemingly depends on crosstalk with the abscisic acid (ABA) signaling network. In the past 2 years, a number of independent studies have revealed that ⋅NO gates the ABA signaling network at multiple steps, ensuring redundant and effectively irreversible control of germination. Here we summarize the recent studies, and propose a model of the multiple functions of ⋅NO in seed dormancy.